A molecular dynamics simulation study of the effect of water–graphene interaction on the properties of confined water. Issue 17 (21st November 2016) - Mozaffari, Farkhondeh
Abstract: The role of water in determining the structure and stability of biomacromolecules has been well studied. In this work, molecular dynamics simulations have been applied to investigate the effect of surface hydrophobicity on the structure and dynamics of water confined between graphene surfaces. In order to evaluate this effect, we apply various attractive/repulsive water–graphene interaction potentials (hydrophobicity). The properties of confined water are studied by applying a purely repulsive interaction potential between water–graphene (modelled as a repulsive r −12 potential) and repulsive–attractive forces (modelled as an LJ(12-6) potential). Compared to the case of a purely repulsive graphene–water potential, the inclusion of repulsive–attractive forces leads to formation of sharp peaks for density and the number of hydrogen bonds. Also, it was found that repulsive–attractive graphene–water potential caused slower hydrogen bonds dynamics and restricted the diffusion coefficient of water. Consequently, it was found that hydrogen bond breakage and formation rate with the repulsive r −12 potential model, will increase compared to the corresponding water confined with the LJ(12-6) potential.